SINERGI LEADERSHIP DAN ENTREPRENEURSHIP DALAM PERSPEKTIF BELA NEGARA UNTUK MEMPERKUAT KETAHANAN NASIONAL - Akbar Tri Prakoso; Ninis Herawati; Taufikurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study examines the synergy between leadership and entrepreneurship from the perspective of national defense to strengthen national resilience. The primary objective is to identify how the concepts of leadership and entrepreneurship can contribute to shaping a more resilient national character in social, economic, and political contexts. The methodology employed includes literature studies, interviews, and surveys with relevant stakeholders. The results indicate that the synergy between leadership and entrepreneurship can enhance the ability of the younger generation to innovate, make effective decisions, and contribute to national development. Recommendations proposed include improving educational programs, fostering intergenerational collaboration, and utilizing technology in national defense education. Through these measures, it is expected that national resilience will be strengthened, and Indonesia's youth will be better prepared to face global challenges.